Frequent PD-L1 expression in oral squamous cell carcinoma of non-smokers and non-drinkers, and association of tumor infiltrating lymphocytes with favorable prognosis. - FJ Mulder; EJ de Ruiter; TFB Gielgens; F Farshadpour; R de Bree; MFCM van den Hout; B Kremer; SM Willems; EJM Speel (Translational Oncology)
Objectives: To determine the presence and prognostic value of PD-L1 and PD-L2 expression, and tumor-infiltrating lymphocytes (TILs) in oral squamous cell carcinoma (OSCC) of non-smokers and non-drinkers (NSND). Materials and methods: Clinical characteristics and tumor tissue of 86 NSND with OSCC were retrospectively collected and analyzed for protein expression on tissue microarrays. Immunohistochemistry was performed for expression of PD-L1 CPS, PD-L2 TPS, and PD-1, CD45, CD8, CD4, CD3, and FoxP3-positive TILs/mm2. Slides were digitally evaluated using QuPath. Differences in 5-year DFS and OS were determined by log rank analysis. Predictors for survival were determined by multivariable cox regression analysis. Results: Eighty-eight percent (76/86) of OSCC showed PD-L1 expression (CPS ≥1). Patients with high numbers of CD4-positive TILs showed a better DFS and OS than patients with low numbers of CD4-positive TILs. In the best multivariable model, CD4-positive TILs were an independent predictor for DFS (p = 0.010) and OS (p = 0.002) too. Additionally, patients with high numbers of CD45-positive TILs and a high CD8/FoxP3 ratio showed a better OS, of which the CD8/FoxP3 ratio was a near significant independent predictor (p = 0.050). Over 40 % of OSCC were PD-L1+/TIL+. Conclusion: A large number of OSCC in NSND show PD-L1 expression (CPS ≥1). CD4 was a significant predictor for DFS and OS, in addition to the CD8/FoxP3 ratio being a near significant predictor for OS. The combination of frequent high CD8-positive TIL infiltrates in PD-L1-positive tumors makes NSND with OSCC in theory interesting candidates for treatment with immune checkpoint inhibitors.